Improving standards in brain-behavior correlation analyses - Rousselet, Guillaume A.; Pernet, Cyril R. (Frontiers in Human Neuroscience, 2012)
Associations between two variables, for instance between brain and behavioural measurements, are often studied using Pearson correlation. However, Pearson correlation is not robust: outliers can introduce false correlations or mask existing ones. These problems are exacerbated in brain imaging by a widespread lack of control for multiple comparisons, and several issues with data interpretations. We illustrate these important problems associated with brain-behaviour correlations, drawing examples from published articles in mainstream high-impact and specialty journals. We make several propositions to alleviate these problems.